EFEKTIVITAS PEMBELAJARAN SAINS MENGGUNAKAN APLIKASI TEKNOLOGI DI SEKOLAH DASAR NEGERI 1 E’ERINERE - Yola Afrianti; Aspin; Abubakar; Ishak Bagea; Wa Ode Yustin Alfianti (STKIP Subang, 2026)
This study examined the effectiveness of technology application in science learning at SDN 1 E'erinere. The research addressed the problem of low student engagement and difficulty in understanding abstract science concepts under conventional teaching methods dominated by lectures and textbooks. The study aimed to determine the effect of technology-based learning on student learning outcomes and learning motivation. A quantitative approach with a quasi-experimental design was employed, using a nonequivalent control group design. Forty fifth-grade students participated, divided into an experimental group of 20 students who received technology-based instruction and a control group of 20 students taught through conventional methods. Data were collected using multiple-choice tests for pretest and posttest, a Likert-scale questionnaire measuring motivation, and classroom observation. Instruments were validated through expert judgment and tested for reliability before use. Data were analyzed using descriptive statistics and an independent samples t-test, preceded by normality and homogeneity tests. Results showed that the experimental group's posttest scores rose from an average of 60 to 85, compared with an increase from 58 to 75 in the control group, with a significance value of 0.01. The experimental group also recorded a higher average motivation score of 4.21 against 3.48 in the control group. These findings indicate that technology-based learning significantly improves both learning outcomes and motivation among elementary school students. Technology application therefore offers a viable strategy for elementary science education, provided it is supported by teacher readiness and adequate facilities.